Morphometric study of ostrich kidneys Struthio camelus Linnaeus, 1758 - Estruc, Thais Mattos; Nascimento, Renata Medeiros do; Santos-Sousa, Carlos Augusto; Souza Junior, Paulo; Stocco, Anieli Vidal; Pereira, Letícia Victal; Abidu-Figueiredo, Marcelo (Acta Scientiarum. Biological Sciences, 2024)
In recent years, avian medicine has advanced in the recognition of kidney diseases, but little is known about the morphology and renal morphometry of the common ostrich Struthio camelus Linnaeus, 1758. This study aimed to describe the morphometry and location of kidneys in the common ostrich. Twenty-six cadavers, aged one to seven days, which died of natural causes on a farm in the municipality of Magé, state of Rio de Janeiro, Brazil, were donated to the Department of Animal and Human Anatomy at the Universidade Federal Rural do Rio de Janeiro (UFRRJ). The specimens were identified, sexed, and fixed in a 10% aqueous solution of formaldehyde. The kidneys and renal divisions were measured using a precision digital caliper. The kidneys of S. camelus are elongated, and lobular, and have three renal divisions (cranial, middle, and caudal). The average length of the right kidney was 6.69 ± 0.83 cm, and the left kidney was 6.87 ± 0.81 cm. The body length correlated positively and significantly with the lengths of the right kidney (r = 0.8273, p = 0.0017) and left kidney (r = 0.8534, p = 0.0008) in females. The renal cranial limit was observed at the eighth lumbar vertebra (L8) in 22 kidneys (42.3%), and the caudal limit, at the eighth sacrocaudal vertebra (Sc8) in 11 kidneys (21.2%), and the second caudal vertebra (C2) in 11 kidneys (21.2%). The morphometric dimensions and skeletopy of the ostrich kidney contribute to the field of comparative avian anatomy and assist in the interpretation of imaging techniques.